Genetic contribution of CISH promoter polymorphisms to susceptibility to tuberculosis in Chinese children. - Lin Sun (Public Library of Science (PLoS), 2014)
Tuberculosis (TB) is the leading cause of death due to an infectious disease worldwide, particularly in developing countries. A series of candidate genes have been suggested to be associated with development of TB disease. Among them, the human Cytokine-inducible Src homology 2(SH2) domain protein (CISH) gene has been very recently reported to be involved in T cell activation and differentiation in response to Mycobacterium tuberculosis infection. Here, we studied the association between CISH promoter polymorphisms and pediatric TB. A case-control study enrolled 352 TB patients and 527 healthy controls, who were of Han Chinese ethnicity and aged from 0.2 to 18 years. CISH gene promoter SNPs rs414171, rs622502 and rs809451 were genotyped in all subjects and transcriptional activity, mRNA level, and plasma cytokine level of subjects with different genotypes were further examined. Carriers with rs414171TT homozygotes and rs809451GC heterozygotes had a 1.78-fold (95% CI,1.16-2.74) and 1.86-fold (95% CI, 1.26-2.74) excess risk of developing TB compared to those with wild-type genotypes. A greater risk of TB disease was observed in population carrying C(-809451)-T(-414171)-C(-622502) haplotype (OR 3.66, 95% CI:2.12-6.32). The G(-809451)-A(-414171)-C(-622502)-containing CISH promoter drove a 5.43-fold increased reporter expression compared to the C(-809451)-T(-414171)-C(-622502)-containing counterpart in Hela cell lines (P = 0.0009). PBMCs carrying rs414171TT homozygotes and rs809451GC heterozygotes showed a reduced CISH mRNA level compared to cells carrying wild type genotypes. Individuals with the rs414171TT genotype had significantly increased IL-12p40 and IL-10 production. In conclusion, CISH promoter rs414171 and rs809451 polymorphisms may play a vital role in mediating individual susceptibility to tuberculosis.